Microstructure and dielectric properties of (Ba0.6Sr0.4)TiO3/PEEK functional composites prepared via cold-pressing sintering. (1st March 2022) - Liu, Shuhang; Guo, Yiting; Li, Jianwei; Wu, Sichen; Xu, Jie; Pawlikowska, Emilia; Kong, Jie; Rydosz, Artur Maciej; Szafran, Mikołaj; Gao, Feng
Abstract: Ceramic/polymer dielectric functional composites have attracted extensive attention because of their applications in portable electronic devices, filters and other fields. However, the high dielectric loss and the attenuation of dielectric constant with frequency limit the applications. Here, (Ba0.6 Sr0.4 )TiO3 /PEEK (BST/PEEK) composites with high frequency stability of the dielectric constant and low dielectric loss were prepared via cold-pressing sintering. The dielectric frequency stability of BST/PEEK composites was assessed by employing the frequency dispersion factor F (x) . The results showed the BST/PEEK composites possessed the optimal properties with a permittivity of 23, a loss of 0.0065, an F (x) of <5%, and a dielectric tunability of 11.9% when the BST concentration was 40 vol% and the composites were sintered at 360 °C for 1 h. In addition, the numerical fitting results of dielectric constant of composites showed that the Yamada model with a shape factor n of 9.5 would obtain the best simulation result by keeping the relative error lower than 2%. This work provides the idea for obtaining a new composite with low loss and high frequency stability. Graphical abstract: (Ba0.6 Sr0.4 )TiO3 /PEEK functional composites were prepared via cold-pressing sintering and the uniform microstructure was obtained. The dielectric constant of the material had good frequency stability and the dielectric loss remained at a very low level when the frequency was below 10 5  Hz. Different dielectric theoretical models were used to simulate the permittivities of composites, the Yamada model with a shape factor n of 9.5 would get the best simulation results when the volume fraction of BST was over 30%. Image 1 Highlights: (Ba0.6 Sr0.4 )TiO3 /PEEK functional composites were prepared via cold-pressing sintering. The dielectric constant of the material showed good frequency stability with low dielectric loss. The Yamada dielectric model with a shape factor n of 9.5 is in good agreement with experimental results. The dielectric tunability of 11.9% is obtained for BST/PEEK composites.